2021
DOI: 10.1101/2021.03.27.21254107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 N501Y mutation by RT-PCR to identify the UK and the South African strains in the population of South Indian state of Telangana

Abstract: ObjectiveTo detect N501Y mutation of the SARS-CoV-2 spike protein by RT-PCR to distinguish (B.1.1.7) UK and (501Y.V2) South African strains from others in the population of Telangana and to determine its clinical implications.MethodsA primer-probe mix that specifically detects the mutated N501Y strain by real time RT-PCR was designed. 93 samples that were reported positive for COVID-19 by our laboratory in the month of February 2021 were tested using our own primer-probe mix for the presence of N501Y by RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Among them N440K, P681H considered to be powerful having more virulence, infectious and have higher immune escape than the wild type strain. 20,33 N440K mutation in SARS-CoV-2 became the reason behind the major destruction caused by the SARS-CoV-2 in Visakhapatnam, Karnataka, Telangana and other southern parts of India. 20 N501Y mutation found in this study was also detected in Telangana, the southern parts of India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them N440K, P681H considered to be powerful having more virulence, infectious and have higher immune escape than the wild type strain. 20,33 N440K mutation in SARS-CoV-2 became the reason behind the major destruction caused by the SARS-CoV-2 in Visakhapatnam, Karnataka, Telangana and other southern parts of India. 20 N501Y mutation found in this study was also detected in Telangana, the southern parts of India.…”
Section: Discussionmentioning
confidence: 99%
“…20 N501Y mutation found in this study was also detected in Telangana, the southern parts of India. 33 Occurrence of re-infections and rapid transmission is mainly due to the emergence of all these new variants, either after natural infection or after vaccination. 24 A recent study confirmed that re-infections are already happening in India.…”
Section: Discussionmentioning
confidence: 99%